Correlation of three instruments used to assess pain in elderly patients with knee osteoarthrosis in a school clinic in Recife, Pernambuco State, Brasil (Research, Society and Development, 2020)
Introduction: The aging process is a global reality directly affecting the daily tasks and quality of life of the elderly. Due to the increase in population aging, the growth of chronic diseases is observed, with osteoarthrosis (OA) being the most prevalent. Aim: To evaluate the applicability of pain assessment instruments in elderly patients with knee osteoarthrosis. Methods: This is an observational, descriptive cross-sectional study with 22 participants with OA. An evaluation was performed using the socioclinical questionnaire, Visual Analog Scale, Brief Pain Inventory and the McGill Questionnaire. Finally, the data were submitted to statistical analysis considering the significance level of p